2014
DOI: 10.1371/journal.pgen.1004613
|View full text |Cite
|
Sign up to set email alerts
|

Targeted H3R26 Deimination Specifically Facilitates Estrogen Receptor Binding by Modifying Nucleosome Structure

Abstract: Transcription factor binding to DNA in vivo causes the recruitment of chromatin modifiers that can cause changes in chromatin structure, including the modification of histone tails. We previously showed that estrogen receptor (ER) target gene activation is facilitated by peptidylarginine deiminase 2 (PAD2)-catalyzed histone H3R26 deimination (H3R26Cit). Here we report that the genomic distributions of ER and H3R26Cit in breast cancer cells are strikingly coincident, linearly correlated, and observed as early a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 37 publications
1
57
1
Order By: Relevance
“…Several studies from others and us have shown that, in addition to targeting histones [1820], PAD4 can also regulate to function on non-histone proteins via citrullination [2226,29]. We therefore wondered whether PAD1 could modulate MEK1 via similar mechanisms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies from others and us have shown that, in addition to targeting histones [1820], PAD4 can also regulate to function on non-histone proteins via citrullination [2226,29]. We therefore wondered whether PAD1 could modulate MEK1 via similar mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, PAD -mediated protein citrullination has gathered increased attention due to its emerging role in various cancers [17]. For example, PAD2 and PAD4 can catalyze citrullination of histone H3 and H4 at gene promoters, leading to local changes in chromatin structure and modulation of tumor-associated gene transcription in human breast cancer cells [18,19]. PAD4 was also found to mediate citrullination of histone H3 at the apoptosis-related gene promoters in other cancer cells [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…73 The authors further suggest that histone citrullination might be a critical prognostic for ER+ tumor development and is thus suited to stratify ER+ tumors into clinically relevant subsets. This observation also raises the intriguing question of whether histone citrullination may act as either a tumor promoter or a suppressor mark in a context and or isozyme-dependent manner.…”
Section: Histone Citrullination (Arginine Deimination)mentioning
confidence: 99%
“…However, the outcome of such a coactivator function is strongly dependent on the cellular context. In the estrogen receptor-positive subgroup of breast cancer patients, PADI2 expression correlated with good prognosis and in breast cancer cells was shown to facilitate the binding of the estrogen receptor to its target genes (18).…”
Section: Introductionmentioning
confidence: 99%